FINANCIAL ADAPTABILITY AND COMPANY PERFORMANCE OF MINING SECTOR JOINT-STOCK COMPANIES - Ganbat, Khurelbaatar; Sodnomdavaa, Tsolmon; Buyantsogt, Asralt; Dangaa, Ganbat; Ganbat, Lkhamdulam (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
This study examines the relationship between financial adaptability and firm profitability using a panel dataset of 90 firm-year observations from nine coal mining companies listed on the Mongolian Stock Exchange over the period 2015–2024. Financial adaptability is measured by a composite index (FAI) constructed with equal weights from four indicators: current ratio, asset turnover, proportion of short-term assets, and gross profit margin. This study represents an initial attempt to construct a composite measure of financial adaptability for coal mining firms and provides empirical support for dynamic capability theory in the Mongolian context.